Oscillatory motion and merging responses of primary and satellite droplets from Newtonian liquid jets. (2nd February 2020) - Viswanathan, H.
Highlights: Droplet surface oscillations aid partial coalescence leading to  reflexive-like  separation. The  reflexive-like  separation shows  re-merging  of droplets due to undamped surface oscillations. Forward, rear and simultaneous merging of satellites with primary droplets are predicted. A new mode of satellite merging back into the moving jet liquid core is predicted. The formation of air-entrapment is evidenced during coalescence events. Abstract: Numerical simulations of laminar Newtonian liquid jets are presented that divulge several breakup and merging responses for both primary and satellite droplets. Using an axisymmetric VOF model, we predict the presence of surface oscillations of droplets disintegrated from jets, which at times lead to merging of droplets when travelling downstream. Our simulations indicate that when primary droplets undergo merging, they exhibit characteristics such as ( i ) permanent and ( ii ) partial coalescence. We find that the partial coalescence of droplets can lead to a reflexive-like separation and then show re-merge responses. The formation of an air-bubble during the merging of binary droplets is predicted. Characteristics such as forward, rear, and simultaneous merging patterns of satellites with primary droplets are captured in our numerical simulations. Furthermore, a new merging pattern is reported wherein, satellites formed from the swellings of the jet can be absorbed back into the moving core of the liquid jet.